First record for Camponotus vagus (Hymenoptera: Formicidae) in Crete, Greece - García, Fede (ENTOMOLOGIA HELLENICA, 2025)
Camponotus vagus (Scopoli, 1763) is a lignicolous ant species widespread in Europe and Greece, including some large Mediterranean islands. Herein, the first record for the species in the island of Crete is presented.